Elbow arthroplasty research methods, outcome domains, and instruments used in clinical outcome studies: a scoping review. (1st October 2022) - Watts, Adam C.; Hamoodi, Zaid; McDaid, Catriona; Hewitt, Catherine
Abstract : Aims: Arthroplasties of the elbow, including total elbow arthroplasty, radial head arthroplasty, distal humeral hemiarthroplasty, and radiocapitellar arthroplasty, are rarely undertaken. This scoping review aims to outline the current research in this area to inform the development of future research. Methods: A scoping review was undertaken adhering to the Joanna Briggs Institute guidelines using Medline, Embase, CENTRAL, and trial registries, limited to studies published between 1 January 1990 and 7 February 2021. Endnote software was used for screening and selection, and included randomized trials, non-randomized controlled trials, prospective and retrospective cohort studies, case-control studies, analytical cross-sectional studies, and case series of ten or more patients reporting the clinical outcomes of elbow arthroplasty. The results are presented as the number of types of studies, sample size, length of follow-up, clinical outcome domains and instruments used, sources of funding, and a narrative review. Results: A total of 362 studies met the inclusion criteria. Most were of total elbow arthroplasty (246; 68%), followed by radial head arthroplasty (100; 28%), distal humeral hemiarthroplasty (11; 3%), and radiocapitellar arthroplasty (5; 1%). Most were retrospective (326; 90%) and observational (315; 87%). The median sample size for all types of implant across all studies was 36 (interquartile range (IQR) 21 to 75). The median length of follow-up for all studies was 56 months (IQR 36 to 81). A total of 583 unique outcome descriptors were used and were categorized into 18 domains. A total of 105 instruments were used to measure 39 outcomes. Conclusion: We found that most of the literature dealing with elbow arthroplasty consists of retrospective observational studies with small sample sizes and short follow-up. Many outcomes have been used with many different instruments for their measurement, indicating a need to define a core set of outcomes and instruments for future research in this area. Cite this article: Bone Joint J  2022;104-B(10):1148–1155.